2003
DOI: 10.1509/jmkg.67.2.35.18612
|View full text |Cite
|
Sign up to set email alerts
|

To have and to Hold: The Influence of Haptic Information on Product Judgments

Abstract: Haptic information, or information attained through touch by the hands, is important for the evaluation of products that vary in terms of material properties related to texture, hardness, temperature, and weight. The authors develop and propose a conceptual framework to illustrate that salience of haptic information differs significantly across products, consumers, and situations. The authors use two experiments to assess how these factors interact to impair or enhance the acquisition and use of haptic informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
504
5
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 496 publications
(534 citation statements)
references
References 27 publications
(35 reference statements)
17
504
5
8
Order By: Relevance
“…This contemplative behavior is engaged in by individuals with high NFT who chronically access haptic information at the evaluation stage (Peck & Childers, 2003a). Higher NFT individuals are more confident in their judgments when they can touch the product (Peck & Childers, 2003b), and this level of high NFT consumer self-confidence is increased after touching a product previously considered in the online environment (Gurrea & Orús, 2014). Therefore, high NFT individuals also touch the product, thereby evaluating it two-fold and in order to be sure about their judgments and to confirm the value or quality of the product in question (Peck & Childers, 2003a).…”
Section: Research Hypothesesmentioning
confidence: 99%
“…This contemplative behavior is engaged in by individuals with high NFT who chronically access haptic information at the evaluation stage (Peck & Childers, 2003a). Higher NFT individuals are more confident in their judgments when they can touch the product (Peck & Childers, 2003b), and this level of high NFT consumer self-confidence is increased after touching a product previously considered in the online environment (Gurrea & Orús, 2014). Therefore, high NFT individuals also touch the product, thereby evaluating it two-fold and in order to be sure about their judgments and to confirm the value or quality of the product in question (Peck & Childers, 2003a).…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Recently, the Mere Exposure Effect was demonstrated in the haptic modality (Jakesch & Carbon, 2012). It has also been reported that consumers' evaluations of items increase when they are allowed to touch the items (Grohmann, Spagenberg, & Sprott, 2007;Peck & Childers, 2003). The last item sampled tends to have a larger number of touches than the other items.…”
Section: Discussionmentioning
confidence: 98%
“…According to Peck and Childers (2003), the only way to ensure that a product is worth buying is actually to touch it. Bringing this home to the fast food restaurants, Can services be touched?…”
Section: The Power Of Touchmentioning
confidence: 99%